การตรวจวัดอาร์ไนต์ในน้ำเสียจากการขุดเจาะแก๊สธรรมชาติด้วยโวลแทมเมตรี - นริศรา เปรี้ยวน้อย (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Arsenite is the most toxic species, among many forms of inorganic arsenic species presents in environment. Exposure to arsenite can cause a variety of adverse health effects. Short-time arsenite measurement in environmental sample is highly recommended. The arsenite measurement in condensate wastewater from petrochemical industry was investigated in this study. The electrochemical techniques between batch and flow system (SIA) were compared. Signals obtained from square-wave anodic stripping voltammetrie square-wave cathodic stripping voltammetries, Differential-pulse cathodic stripping voltammetrie and square-wave voltammetrie techniques were demonstrated. Bismuth-film, gold-film and silver-film electrodes were employed in comparison with the gold electrode. The result revealed that bismuth-film electrode and square-wave voltammetrie are sultable for monitoring arsenite level in the condensate wastewater at its original pH without the pretreatment step. square-wave voltammetrie was performed under the optimized conditions, 20 mV step potential, 65 mV pulse amplitude, 15 Hz frequency and 0.45 V cleaning step for 6 s. An interfering signal from dissolved oxygen and turbidity of water had no effect to the obtained signal. The calibration curve exhibited a linear range between 0.02 and 300 mg/L. Limit of detection (LOD) and limit of quantitation (LOQ) were found to be 11 g/L and 36 g/L, respectively. An excellent recovery was found in the range of 101.10 - 111.20 % and RSD was lower than 3.55 %.